The Effect of Work From Home on Work Life Balance and Work Stress on Female Workers - Arwin Arwin; Ivone Ivone; Supriyanto Supriyanto; Ruri Aditya Sari (Institute of Computer Science (IOCS), 2021)
At the beginning of the work from home policy, many employees, especially female employees, enthusiastically welcomed it, because they could do office work while taking care of the household. This study aims to analyze the effect of work from home (WFH) on work life balance (WLB) and work stress for female workers in Medan City. Respondents in this study were 100 female workers in the city of Medan aged 25-49 years with purposive snowball sampling technique. Data was collected by distributing a 5 Likert scale questionnaire. The analysis carried out in this study was a partial and simultaneous test of the influence between variables. Based on the results of the study showed that there was an influence (p>0.05) betweenWFH with WLB and work stress simultaneously. Meanwhile, based on the results of the t test, it shows that WFH does not affect work stress. Furthermore, there were 48% of respondents who gave a doubtful response to their satisfaction in carrying out office and home work during WFH and as many as 35% did not experience role stress during WFH, as many as 19% of female workers in Medan City felt stressed with working conditions during WFH. This study shows that it is necessary to take a policy so that WLB and work stress on female workers do not affect performance.